A Feasibility Study of Microbialites as Paleomagnetic Recorders - Jung, Ji-In; Bowles, Julie A. (Frontiers in Earth Science, 2021)
Microbialites – layered, organosedimentary deposits – exist in the geologic record and extend back in deep time, including all estimated times of inner core nucleation, and may preserve magnetic field variations at high-resolution based on their estimated growth rates. Previous studies have shown that microbialites can have a stable magnetization. However, the timing and origin of microbialite magnetization were not well determined, and no study has attempted to evaluate whether actively growing microbialites record the geomagnetic field. Here we present centimeter-scale magnetization and magnetic property variations within the structure of actively growing microbialites from Great Salt Lake (GSL), USA, and Laguna Bacalar, Mexico, Pleistocene microbialites from GSL, and a Cambrian microbialite from Mongolia. All samples record field directions close to the expected value. The dominant magnetic carrier has a coercivity of 35-50 mT and unblocking temperatures are consistent with magnetite. A small proportion of additional high coercivity minerals such as hematite are also present, but do not appear to contribute to the natural remanent magnetization (NRM). Magnetization is broadly consistent along microbialite layers, and directional variations correlate with the internal slope of the layers. These observations suggest that the documented NRM may be primarily detrital in origin and that the timing of magnetization acquisition is close to that of sediment deposition.